Pengaruh Persepsi Kemudahan, Risiko, dan Iklan terhadap Minat Gen Z Boyolali dalam Menggunakan Dompet Digital - Hilma Agustina; Dianing Widya Kusumastuti (AKUNTANSI 45, 2025)
The objective of this research is to examine how perceived ease of use, perceived risk, and advertising appeal impact the willingness of Generation Z individuals in Boyolali Regency to adopt digital wallets. The investigation stems from the swift expansion of digital financial innovations among youthful consumers, who demonstrate strong technological adaptability but remain wary of issues related to data protection and transactional uncertainties. Employing a quantitative explanatory approach, the study gathered primary information via an internet-based questionnaire utilizing a Likert scale, administered to 100 participants chosen via purposive sampling. Analytical procedures encompassed assessments of validity, reliability, classical assumption checks, and multiple linear regression analysis conducted with SPSS version 25. Findings indicate that perceived ease of use and advertising appeal exert positive and substantial influences on the inclination to utilize digital wallets, while perceived risk demonstrates a negative and noteworthy impact. These outcomes bolster the Theory of Planned Behavior by underscoring the significance of cognitive and emotional elements in molding attitudes toward embracing digital financial solutions. In practical terms, the research stresses the necessity of crafting intuitive interfaces, bolstering protective measures, and deploying innovative promotional tactics tailored to the traits of Generation Z to boost the uptake of digital wallets in semi-urban settings.